2016
DOI: 10.1007/s10439-016-1628-0
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale Modeling of the Cardiovascular System: Disease Development, Progression, and Clinical Intervention

Abstract: Cardiovascular diseases (CVDs) are the leading cause of death in the western world. With the current development of clinical diagnostics to more accurately measure the extent and specifics of CVDs, a laudable goal is a better understanding of the structure-function relation in the cardiovascular system. Much of this fundamental understanding comes from the development and study of models that integrate biology, medicine, imaging, and biomechanics. Information from these models provides guidance for developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 180 publications
(187 reference statements)
0
33
0
Order By: Relevance
“…The goal of this third point is to lay the foundations for the development of a predictive model that can reproduce animal experimental evidences that were retrieved by our group in a recent publication (Zhang Y et al 2016). The innovative predictive model will be characterized by a level of complexity between multiple scales and adaptation mechanisms that will go beyond our present controlled and simplified “theoretical biology” experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The goal of this third point is to lay the foundations for the development of a predictive model that can reproduce animal experimental evidences that were retrieved by our group in a recent publication (Zhang Y et al 2016). The innovative predictive model will be characterized by a level of complexity between multiple scales and adaptation mechanisms that will go beyond our present controlled and simplified “theoretical biology” experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Despite this, partial reviews can be found in other works. 10,66,67 These fluid-electro-mechanical models solve the three set of equations in a coupled manner. Now, we present a brief insight on each one of the three-physics models in existence.…”
Section: Coupled Multi-physics Cardiac Computational Modeling State Omentioning
confidence: 99%
“…The reason for this is, probably, the scarcity of such models. Despite this, partial reviews can be found in other works . These fluid‐electro‐mechanical models solve the three set of equations in a coupled manner.…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers can identify individuals with an increased cardiovascular risk, and biomarker-guided therapy represents an attractive option, with troponin-guided therapy of acute coronary syndromes as a successful example [55] . Multiscale modeling of cardiac electrophysiology and mechanics for diagnosis as well as clinical decision support will facilitate the development of personalized cardiology, e.g., in arrhythmia and HF [56] . The introduction of new technologies such as high-resolution CT coronary imaging with fractional flow reserve, virtual reality, vascular robotic systems, and 3-D printing can be incorporated into personalized care to improve the efficacy as well as the safety of the treatment of patients with CVD [57] .…”
Section: Concluding Remarks and The Future Of Personalized Cardiologymentioning
confidence: 99%